Prevalence and etiology of midfacial fractures: A study of 799 cases - Linas Zaleckas; Vytautė Pečiulienė; Ieva Gendvilienė; Alina Pūrienė; Jūratė Rimkuvienė (Medicina, 2015)
Background and objective: The prevalence and etiology of midfacial fractures varies among countries. Until now, knowledge about such type of injuries in the region of the Baltic countries was rather scarce. The purpose of the study was to analyze the prevalence, etiology and localization of midfacial fractures treated at the Vilnius University Hospital Žalgiris Clinic, Vilnius, Lithuania. Materials and methods: The medical records of patients treated for midfacial fractures during the period January 2005 to December 2010 were analyzed for gender, age distribution, frequency and type of injury, cause of fractures, consciousness status and alcohol abuse during trauma. Results: The records of 799 patients were analyzed. The male-to-female ratio was 4.4:1. The mean age of the patients was 33.16 ± 14.0 years (min 1, max 87). As much as 68.8% of injuries were zygomatic fractures, 27.9% were maxillary, and 3.3% were isolated orbital floor fractures. The most frequent causes for injury were interpersonal violence (64%), followed by falls (16.3%) and traffic accidents (8.3%). Most midfacial fractures (65.3%) occurred between April and October (P < 0.05), on weekends (58.2%; P < 0.05) and at night (62.0%; P < 0.05). In 14%, trauma reports indicated the abuse of alcohol. More often such persons received more than one midfacial bone fracture (P < 0.05) concurrently. Conclusions: This study revealed that the main cause of midfacial fractures was assault. Male patients, aged 15–34 years, more often sustain midfacial fractures. Preventive health care programs should seek measures in the reduction of aggression and violence in close future involving family, school and community institutions.